INTERNATIONAL SCHOOL OF FINANCE TECHNOLOGY AND SCIENCE NON-PROFIT HIGHER EDUCATION INSTITUTION - Khayrullayeva Zarnigor Sarvar qizi (Zeta Repository, 2023)
The article analyzes the importance of social networks in the formation of young people and their aesthetics, the types of social networks and their use statistics. The role and use of social networks in the lives of young people. Online and offline aesthetic laws for the use of cellular devices. The contribution of social networks to the formation of youth aesthetics.